Bipolar disorder and/or creative bipolarity: Robert Schumann's exemplary psychopathology - combining symptomatological and psychosocial perspectives with creativity research - Holm-Hadulla, Rainer M.; Koutsoukou-Argyraki, Asimina (Psychopathology, 2017)
The psychopathological condition of Robert Schumann has been a prominent object of study in psychiatry since his hospitalization in 1854. Renowned psychiatrists have diagnosed Schumann with syphilis, schizophrenia, and bipolar and personality disorders. Until today, these analyses of his symptomatology have led to contradictory results. Recent discussion has suggested that his hospitalization was due to professional failure and separation wishes on the part of his wife, her family, and her friends. In line with this hypothesis is the opinion that the separation insisted upon by Clara Schumann was reinforced by the economic interests of the psychiatrist who kept Schumann in custody for 2 years until his death in 1856. In this article, we trace the complex interaction of bipolar vulnerability and pathogenic life events with hypersensitive talent and “creative bipolarity,” defined as the capacity, motivation, and resilience to transform emotional stress and cognitive inconsistency into coherent artistic products. Finally, we present our conclusions about comprehensive psychiatric and psychotherapeutic treatment with respect to “creative bipolarity.”